2013
DOI: 10.4269/ajtmh.2012.12-0371
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight in Offspring of Mothers with High Prevalence of Helminth and Malaria Infection in Coastal Kenya

Abstract: Abstract. Results of studies on the associations of maternal helminth infection and malaria-helminth co-infection on birth outcomes have been mixed. A group of 696 pregnant women from the Kwale district in Kenya were recruited and tested for malaria and helminth infection at delivery. Birthweight was documented for 664 infants. A total of 42.7% of the mothers were infected with Plasmodium falciparum, 30.6% with Schistosoma haematobium, 36.2% with filariasis, 31.5% with hookworm, and 5.9% with Trichuris trichiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…From January 1, 2006, to December 31, 2009, the study team recruited pregnant women who attended prenatal care at Msambweni District Hospital, Msambweni, Coast Province, Kenya—a rural area where malaria is endemic [5]. Per Kenya Ministry of Health national policy, women received IPTp beginning in the second trimester, as well as iron, folic acid, and bed nets, as part of routine care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From January 1, 2006, to December 31, 2009, the study team recruited pregnant women who attended prenatal care at Msambweni District Hospital, Msambweni, Coast Province, Kenya—a rural area where malaria is endemic [5]. Per Kenya Ministry of Health national policy, women received IPTp beginning in the second trimester, as well as iron, folic acid, and bed nets, as part of routine care.…”
Section: Methodsmentioning
confidence: 99%
“…Malaria in pregnancy causes low birth weight, a major contributor to neonatal mortality and morbidity worldwide [1–5]. In Sub‐Saharan Africa, where malaria is endemic, malaria in pregnancy may contribute to 25% of low birth weight [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Guatemala City found that helminth and protozoa were associated with risk of small birth weight for gestational age, but only in undernourished women, with undernourishment determined based on maternal height 64. In contrast to these studies, other studies of helminths alone have found no association between infection and birth weight65 or have actually found that women with infections have higher birth weights even in the presence of coinfections 66…”
Section: Premature Birth and Low Birth Weightmentioning
confidence: 79%
“…9 Though an association of low birth weight has been suggested with parasitic zoonoses, it has not been completely established. 10 Ivermectin, a macrocyclic lactone antibiotic is the most effective agent for management of this infection. 4 Though it is a potentially foetotoxic and embryotoxic agent, previous reports of its successful use in pregnancy with no adverse feto-maternal effects exist.…”
Section: Discussionmentioning
confidence: 99%